Transcriptional and post-transcriptional regulation of the pregnane X receptor: a rationale for interindividual variability in drug metabolism - Smutny, Tomas; Hyrsova, Lucie; Braeuning, Albert; Ingelman-Sundberg, Magnus; Pavek, Petr (Archives of toxicology, 2021)
The pregnane X receptor (PXR, encoded by the NR1I2 gene) is a ligand-regulated transcription factor originally described as a master regulator of xenobiotic detoxification. Later, however, PXR was also shown to interact with endogenous metabolism and to be further associated with various pathological states. This review focuses predominantly on such aspects, currently less covered in literature, as the control of PXR expression per se in the context of inter-individual differences in drug metabolism. There is growing evidence that non-coding RNAs post-transcriptionally regulate PXR. Effects on PXR have especially been reported for microRNAs (miRNAs), which include miR-148a, miR-18a-5p, miR-140-3p, miR-30c-1-3p and miR-877-5p. Likewise, miRNAs control the expression of both transcription factors involved in PXR expression and regulators of PXR function. The impact of NR1I2 genetic polymorphisms on miRNA-mediated PXR regulation is also discussed. As revealed recently, long non-coding RNAs (lncRNAs) appear to interfere with PXR expression. Reciprocally, PXR activation regulates non-coding RNA expression, thus comprising another level of PXR action in addition to the direct transactivation of protein-coding genes. PXR expression is further controlled by several transcription factors (cross-regulation) giving rise to different PXR transcript variants. Controversies remain regarding the suggested role of feedback regulation (auto-regulation) of PXR expression. In this review, we comprehensively summarize the miRNA-mediated, lncRNA-mediated and transcriptional regulation of PXR expression, and we propose that deciphering the precise mechanisms of PXR expression may bridge our knowledge gap in inter-individual differences in drug metabolism and toxicity.
Keywords: pregnanový X receptor; Genotype; Phenotype; Gene expression; posttranskripční úpravy RNA; Post-transcriptional regulation; Pregnane X receptor; farmakogenetika; CYP3A4; Transcription, Genetic; lidé; genotyp; biologická variabilita populace; Biological Variation, Population; Pharmacogenomic Variants; microRNA; Non-coding RNA; genetická transkripce; Pregnane X Receptor; RNA Processing, Post-Transcriptional; RNA, Long Noncoding; biotransformace; farmakogenomické varianty; mikro RNA; Pharmacogenetics; Biotransformation; MicroRNAs; fenotyp; RNA dlouhá nekódující; Humans